Hot recycling of asphalt pavement (FHWA-OK-82-4) 405 - (:unkn) unknown (My University, 1982)
The objective of this report is to evaluate the feasibilitly and benefit of utilizing asphalt pavement hot recycling in Oklahoma. The work began in April, 1980 and lasted through June 1980. The 8 1/2 mile (13.6 km) project was located on I-40 in Caddo County. The project involved cold milling the top one inch (25 mm) of roadway. A non-woven polypropylene fabric, Petromat, was placed on the cold milled surface. This material was overlaid with 1 1/2 inches (38 mm) of the hot recycled mixture containing recycled asphalt concrete, virgin aggregate, and asphalt cement.
Keywords: Asphalt pavement; Cold milling; Fabric; Recycled material